Wet chemical etching of cadmium telluride photovoltaics for enhanced open-circuit voltage, fill factor, and power conversion efficiency - Bastola, Ebin; Alfadhili, Fadhil K.; Phillips, Adam B.; Heben, Michael J.; Ellingson, Randy J. (Journal of materials research, 2019)
Cadmium telluride (CdTe) is one of the leading photovoltaic technologies with a market share of around 5%. However, there still exist challenges to fabricate a rear contact for efficient transport of photogenerated holes. Here, etching effects of various iodine compounds including elemental iodine (I 2 ), ammonium iodide (NH 4 I), mixture of elemental iodine and NH 4 I (I − /I 3 − etching), and formamidinium iodide were investigated. The treated CdTe surfaces were investigated using Raman spectroscopy, X-ray diffraction (XRD), scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The CdTe devices were completed with or without treatments and tested under simulated AM1.5G solar spectrum to find photoconversion efficiency (PCE). Based on Raman spectra, XRD patterns, and surface morphology, it was shown that treatment with iodine compounds produced Te-rich surface on CdTe films, and temperature-dependent current–voltage characteristics showed reduced back barrier heights, which are essential for the formation of ohmic contact and reduce contact resistance. Based on current–voltage characteristics, the treatment enhanced open-circuit voltage ( V OC ) up to 841 mV, fill factor (FF) up to 78.2%, and PCE up to 14.0% compared with standard untreated CdTe devices ( V OC ∼ 814 mV, FF ∼ 74%, and PCE ∼ 12.7%) with copper/gold back contact.